Leadership In Inclusive Education: Improving Pedagogic Competence Guidance Of Special Supervisory Teachers - Sayem, Sayem; Akbar, Sa’dun; Arifin, Imron (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This research was conducted to dissect the role of school principals in improving the pedagogic competence of special assistant teachers (GPK) in implementing an inclusive education system. Inclusive education is part of the education system that provides access to equal education, especially for children with limitations and special needs. The increasing number of schools that implement inclusive education simultaneously provides a big challenge, especially related to the pedagogical ability of special assistant teachers to provide learning for children with special needs in the kindergarten environment. This research was conducted using a qualitative approach and a type of case study research to explore the role of school principals in providing pedagogical briefings to special assistant teachers. The data used in the study was collected through several sources, including interviews, observations, and documentation. The results captured from this study show that school principals have a central role in guiding special assistant teachers through coaching to improve their teaching competence and, at the same time, the quality of educational services. Through the research carried out, as well as providing implications related to the importance of schools in ensuring that the learning process with an inclusive education system can run effectively and contribute to further activities and development related to inclusive education, especially at the kindergarten education level.